Wafering of ultra‐thin silicon substrates by MeV hydrogen implantation: effects of fluence and energy. Issue 10 (11th July 2016) - Kuisseu, Pauline Sylvia Pokam; Pingault, Timothée; Ntsoenzok, Esidor; Regula, Gabrielle; Mazen, Frédéric; Sauldubois, Audrey; Andreazza, Caroline
Abstract: In this paper, we report on implantation parameters allowing the delamination of large surface of ultra‐thin silicon substrates by using MeV hydrogen implantation. We particularly focus on the effects of both hydrogen fluence and implantation energy, on the size of the largest delaminated surface in one piece. We demonstrate that thin silicon substrates with thicknesses between 30 µm and 70 µm can be extracted from silicon commercial wafers. In this study, the used‐material, the implantation energy and the hydrogen fluence ranges are (100) Si, 1.5 MeV‐2.5 MeV, 1×10 17 cm –2 ‐2×10 17 cm –2, respectively. We find that, by increasing hydrogen fluence, the maximum achievable surface of delaminated substrates in one piece can be doubled. Indeed, by XTEM, we observed that fracture precursor defects are mostly oriented along {111} in the case of the lowest fluence, which are unfavorable for a good surface‐parallel crack propagation. For the highest fluence, precursors are oriented along {100} which are parallel to the substrate surface, therefore they allow propagation over longer distances of cracks parallel to the substrate surface. We also find that, despite of the raise of the proportion of precursors oriented along {111}, the total surface of delaminated substrates significantly increases with the implantation energy. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)